Sistemática molecular de Leptophlebiidae (Ephemeroptera) neotropical - Monjardim, Marina (2017)
Leptophlebiidae is the largest family of Ephemeroptera in number of genera and the second largest in number of species. Among the biogeographic regions, the Neotropical is the most diversified, with 40% of all species in the family. In this region, it is estimated that 60% of the genera and 80% of the species are endemic. Leptophlebiidae is one of the most studied groups of Ephemeroptera in Neotropical, having been divided in several complexes during the decades of 1980 and 1990, based exclusively on morphological characters. However, for many of the complexes, no one or few studies have been realized since the original propositions. Thus, the present study aimed to verify the cladistic relations and the taxonomic status of the complexes of Leptophlebiidae that occur in the Neotropical Region. Using two molecular markers: Cytochrome Oxidase subunit I (COI, 394 pb) and the D2-D3 region of 28S ribosomal DNA (28SDNAr, 1.231 pb). The data were composed of 155 taxa belonging to 53 genera, of which 29 are Neotropical, representing 70.7% of the Neotropical diversity of family. Our analyzes of Bayesian Inference (IB) and Maximum Likelihood (ML) recovered Netopropical Leptophlebiidae in four distinct clades with high support values (clade IV-VII), each proposed as a subfamily: Terpidinae (clade IV), with exclusively Neotropical representatives (Shield Guyana and Brazil); Choroterpinae (clade V) divided into Choroterpini and Thraulini; Atalophlebiinae (clade VI), with representatives of Madagascar, Australian and Neotropical (Patagonian Shield); And Hagenulinae (clade VII), with exclusively Neotropical representatives (Shield Guyana and Brazil), having been divided into two tribes, Haguenulini and Thraulodini, and five subtribes.